A utilizing efficiency estimation method for wave-driven unmanned surface vehicle. (15th September 2018) - Liu, Peng; Su, Yumin; Liu, Fushun; Liu, Yebao; Zhang, Jianhua; Huang, Shuling
Abstract: A wave-driven unmanned surface vehicle (WUSV) can sail on the sea simply by utilizing wave energy as its driving power. Recently, many studies have been performed on practical applications of oceanic scientific exploration by a WUSV, where the estimation criterion of the navigation performance of the WUSV is always its sailing velocity, although this method is very intuitive but not effective in analyzing the shortcomings in the design of the WUSV. On this basis, a new estimation method, which focuses on the efficiency of utilizing wave energy by the WUSV, is proposed in this paper. The theoretical contribution of this paper is that a generalized solution function for the efficiency of utilizing wave energy is obtained and is expressed in the form of the product of several non-dimensional parameters. In detail, algorithms to calculate input power, i.e., wave energy harvested by the surface float, and usable power, i.e., the product of sailing velocity and thrust force, have been developed. The other development presented in this paper is the proposal of some effective ways to improve the ability of the WUSV to utilize wave energy. Then, numerical simulations are carried out to validate the proposed method, and corresponding experiments are employed to investigate the performance of the method. The results show that the four major factors to impact the ability of the WUSV utilize wave energy are the thrust force of the propulsor, the sailing velocity of the WUSV, the principal dimensions of structures and the wave environment parameters. Summarizing the analysis in numerical validations and experimental studies, the WUSV can generally achieve higher efficiency in utilizing wave energy when it sails in a specific wave environment with certain parameters. Meanwhile, the utilization efficiency of the WUSV is not always much higher, and the reasons for this phenomenon mainly include two aspects: (1) most of the wave energy harvested by the surface float is used to work against the calm water resistance of the propulsor and the umbilical cable; and (2) based on the current design, the motions of the surface float cannot fully respond to the waves. Therefore, an integrated optimizing design for the propulsive and resistance performance of the propulsor, as well as the motion response and resistance performance of the float, will be an effective way to improve the ability of the WUSV to utilize wave energy. In addition, the differences in the sailing velocity and heaving amplitude of foils cause different curve trends for the utilizing efficiency between numerical simulations and experiments. Highlights: A method of estimating wave energy utilizing efficiency for the WUSV is proposed. Effective ways are put forward to improve the ability of the WUSV utilizing wave energy. There are four major factors affecting the WUSV utilizing wave energy. WUSV can achieve higher wave energy utilizing efficiency when wave length is equal to 100 times wave amplitude. The resistance of the TFP and the umbilical cable take most part of total that for the WUSV.